Compliance with the 24-hour movement behaviour guidelines among children and adolescents with disabilities: a systematic review and meta-analysis - Yaru Hao; Xiaogang Zhou; Rizal Razman; Sanying Peng; Nor Shafrin Ahmad (BMC, 2024)
Abstract Background Compliance with the 24-Hour Movement Guidelines (24-HMG: physical activity (PA), screen time (ST), and sleep) has been associated with numerous beneficial health outcomes among children and adolescents. However, there is a lack of consensus on the overall compliance with the 24-HMG specifically among children and adolescents with disabilities. Therefore, this systematic review and meta-analysis aimed to examine the extent to which children and adolescents with disabilities adhere to the 24-HMG globally. Method Quantitative studies published in English until May 2023 were sought by searching seven electronic databases: Web of Science, PubMed, SPORTDiscus, CINAHL, MEDLINE, Scopus, Psychology and Behavioural Sciences Collection. This review included studies that identified participants as individuals with disabilities and reported the overall (non) compliance with the 24-HMG among children and adolescents with disabilities. Results A total of 13 studies, involving 21,101 individuals (65.95% males), aged 6 to 21 years from 9 countries, were included in the analysis. In general, 7% (95%CI: 0.05-0.09, p < 0.01) of children and adolescents with disabilities met all three 24-HMG, while 16% (95%CI: 0.13-020, p < 0.01) did not meet any of the three recommendations. Regarding adherence to individual 24-hour movement behaviour, the rates of compliance were 22% (95%CI: 0.18-0.25, p < 0.01) for PA, 49% (95%CI: 0.41-0.56, p < 0.01) for ST, and 59% (95%CI: 0.56-0.61, p < 0.01) sleep. In relation to numbers of those meeting the 24-HMG, 43% (95%CI: 0.41-0.45, p < 0.01) met one guideline, while 32% (95%CI: 0.28-0.36, p < 0.01) met two guidelines. Conclusion There is a notable percentage of children and adolescents with disabilities who do not meet the recommended the 24-HMG, which encompasses PA, ST, and sleep. This underscores the pressing requirement to create and execute evidence-based strategies that effectively encourage and assist these individuals with disabilities in adopting and maintaining these movement behaviours.